Aktivitas Public Relations Dalam Membangun Kerjasama Dengan Stakeholders (Studi Fungsi dan Peran Public Relations di Sekolah Pascasarjana UIN Jakarta) - Nurbaini Futuhat Wulansari (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2021)
As an organization of education providers, an institution needs to manage a positive image either an internal or external public. Discussion about an image will be related to an activity and role of public relations in institutions. Public trust in education aspect can be seen from the role of public relations how to maintain and manage positive image. Graduate School State Islamic University of Syarif Hidayatullah (UIN) Jakarta is the oldest Master and Doctor Study program in Indonesia, and it was endorsed under the decree by The Ministry of Religious Affairs in 1982. The objectives of this research is not only to find out an activities of public relations but also to explain an obstacles, challenges and achievements which is conducted by public relations activities at Graduate School UIN Jakarta. This research uses qualitative approach using Triangulation method with descriptive in-depth interview and observation. Researcher believes that it can be described and summarize various condition, situation or various phenomenon. The data for the research were collected using depth interview and documentation techniques. Public relations activity has tendency to practice of public information, which is used one-way communication model in form of dissemination news, scientifically activities and there is no significant stages. The results of this study concluded an activity of public relations have run optimally but it is simply for public information and doing no evaluation. Obstacles and challenges in building international cooperation are limitedness funds, and due to official travel permits from governments made difficulties in dealing particularly with foreigner stakeholders. Furthermore, factor of human resources causes of lack in networking collaboration and an achievement are doing right but still there is no significant changes and only for permeate the budget optimally.